Confirmatory Factor Analysis (CFA) Method in Factor Analysis at BMT NU Cluring Banyuwangi Branch - Badriyah, Lutfi Lailatul; Ekaningsih, Lely Ana Ferawati (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the factors that influence the interest of partners in saving at BMT NU Cluring Branch using the Confirmatory Factor Analysis (CFA) method. The type of quantitative research with an ex-post-facto approach, sampling using probability sampling with Simple Random Sampling approach, involving 68 respondents. The results of the analysis show that service factors (X1), trust (X2), location (X3), religiosity (X4), and products (X5) have a significant influence on interest in saving (Y). Quality and fast service factors (X1), high level of trust in BMT NU (X2), strategic location (X3), strong community support (X4), and efficient and attractive products (X5) have been proven to increase partner interest. In addition, high transactional interest is a dominant indicator in showing the strong desire of customers to manage their finances. Overall, the results of this study confirm that the indicators in the independent variables consistently influence the savings interest of partners at BMT NU Cluring Branch, which is reflected in the CFA results.